2018
DOI: 10.5493/wjem.v8.i3.18
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs as biomarkers for diabetic neuropathy: A novel approach

Abstract: Oxidative stress stemming from tissue exposure to constant hyperglycemia is one of the major pathogenetic pathways of diabetic macro- and microvascular complications. Diabetic polyneuropathy, commonly manifesting as distal, symmetrical sensorimotor polyneuropathy, is characterized by progressive severity of symptoms, with rates analogous to the quality of glycemic control achieved by the patients and physicians. Palliative care with analgesics and aggressive glycemic control often improve quality of life in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“… 5 The key involvement of microRNAs (miRNAs or miRs) in diabetes and its complications, which is by regulating multiple biological pathways, has been highlighted in several studies. 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“… 5 The key involvement of microRNAs (miRNAs or miRs) in diabetes and its complications, which is by regulating multiple biological pathways, has been highlighted in several studies. 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…In the context of diabetes, hyperglycemia, hypoxia, and inflammation affect miRNA biogenesis and release. Consequently, these alterations in the miRNA profile are associated with multiple microvascular complications (20)(21)(22)(23). Of note, a significant portion of miRNAs was found to be specifically packaged into extracellular vesicles that express cell-type-specific proteins to mediate their different functions (24).…”
Section: Function Of Micrornasmentioning
confidence: 99%
“…They found that miR-17-1-3p, miR-330-5p, and miR-346 are potent promoters of DN (113). Xourgia et al proposed that miR-146, miR-499a, and miR-199a-3p are possible biomarkers of DN (21). In addition, miR-181a-1, miR-541, miR-341, and miR-203 were reported to be dysregulated in an animal model of DN (116).…”
Section: Mirnas As Biomarkers In the Diagnosis Of Diabetic Neuropathymentioning
confidence: 99%
“…In addition, distinct circulating miRNA profiles between subjects with obesity and T2D aroused considerable attention given their potential as biomarkers for these diseases. Indeed, strong correlations were found between some circulating miRNAs and the development of metabolic syndrome [ 59 ], obesity [ 60 , 61 ], diabetes [ 32 , 62 , 63 ] and/or linked to CVD [ 37 , 64 ]. Nowadays, miRNAs are attractive candidates as innovative biomarkers and have been proposed to promote the progression to diabetes [ 29 , 33 , 62 ].…”
Section: Mirnas and Cardiovascular Risk Factors (Crfs)mentioning
confidence: 99%